The amplified circularly polarized luminescence regulated from D–A type AIE-active chiral emitters via liquid crystals system. Issue 7 (2nd January 2020) - Li, Yang; Liu, Kerui; Li, Xiaojing; Quan, Yiwu; Cheng, Yixiang
Abstract : Two pairs of D–A type AIE-active chiral dyes doped into host 5CB form N*-LCs and regulate the amplified CPL signals. R -/ S -2 with stronger D–A structure and more planar conformation could induce higher CPL response ( g lum = ±0.37) in N*-LCs system. Abstract : Two pairs of D–A type AIE-active chiral dyes ( R -/ S -1 and R -/ S -2) as chiral emitters doped into nematic liquid crystals (5CB, N-LCs) can form chiral nematic liquid crystals (N*-LCs) and regulate the amplified circularly polarized luminescence (CPL) signals. R -/ S -2 with stronger D–A structure and more planar conformation could induce higher CPL response ( g lum = ±0.37) via the supramolecular self-assembly in N*-LCs system.